Fostering Behavioral Engagement Using Problem-Based Learning in a group of Night School Students in El Santurario, Antioquia (2023)
ABSTRACT : This action research aimed at fostering the behavioral engagement towards the English class by using Problem-Based Learning, in a group of night school students. It was conducted in a public institution located in El Santuario, Antioquia. The actions implemented used the 6-step cycle proposed by Problem-Based Learning, accompanied by the development of activities to improve positive conduct and involvement of academic tasks. Data instruments used were journal entries, students’ artifacts mainly written reflections and a checklist. Findings revealed that Problem-Based Learning help to foster students’ conduct by increasing their interest and involvement in class by following instructions, asking questions, and contributing to class discussions.